2014
DOI: 10.1042/bsr20140149
|View full text |Cite
|
Sign up to set email alerts
|

The proline-rich region of 18.5 kDa myelin basic protein binds to the SH3-domain of Fyn tyrosine kinase with the aid of an upstream segment to form a dynamic complexin vitro

Abstract: The intrinsically disordered 18.5 kDa classic isoform of MBP (myelin basic protein) interacts with Fyn kinase during oligodendrocyte development and myelination. It does so primarily via a central proline-rich SH3 (Src homology 3) ligand (T92–R104, murine 18.5 kDa MBP sequence numbering) that is part of a molecular switch due to its high degree of conservation and modification by MAP (mitogen-activated protein) and other kinases, especially at residues T92 and T95. Here, we show using co-transfection experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 87 publications
3
21
0
Order By: Relevance
“…MBP takes part in several protein-protein interactions, and thus acts as an effector. MBP interacts with Fyn kinase [78][79][80], cytoskeletal elements [78,81], and calmodulin, the latter interaction being dependent on Ca 2+ [21,[82][83][84]. The interaction with Fyn kinase is mediated via the SH3 domain, which MBP binds through a conserved PXXP motif.…”
Section: Myelin Basic Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…MBP takes part in several protein-protein interactions, and thus acts as an effector. MBP interacts with Fyn kinase [78][79][80], cytoskeletal elements [78,81], and calmodulin, the latter interaction being dependent on Ca 2+ [21,[82][83][84]. The interaction with Fyn kinase is mediated via the SH3 domain, which MBP binds through a conserved PXXP motif.…”
Section: Myelin Basic Proteinmentioning
confidence: 99%
“…The interaction with Fyn kinase is mediated via the SH3 domain, which MBP binds through a conserved PXXP motif. The interaction has a potential impact on oligodendrocytic differentiation, as Fyn signaling is important during myelin development [79,80]. Oligodendrocyte process growth is thought to be modulated by the interaction of MBP with the cytoskeleton [78,81], which in turn is affected by the interaction between MBP and calmodulin [21,85].…”
Section: Myelin Basic Proteinmentioning
confidence: 99%
“…MBP takes part in several protein-protein interactions, and thus acts as an effector. MBP interacts with Fyn kinase [78][79][80], cytoskeletal elements [78,81], and calmodulin, the latter interaction being dependent on Ca 2+ [21,[82][83][84]. The interaction with Fyn kinase is mediated via the SH3 domain, which MBP binds through a conserved PXXP motif.…”
Section: Myelin Basic Proteinmentioning
confidence: 99%
“…The interaction with Fyn kinase is mediated via the SH3 domain, which MBP binds through a conserved PXXP motif. The interaction has a potential impact on oligodendrocytic differentiation, as Fyn signalling is important during myelin development [79,80]. Oligodendrocyte process growth is thought to be modulated by the interactions of MBP with the cytoskeleton [78,81], which in turn is affected by the interaction between MBP and calmodulin [21,85].…”
Section: Myelin Basic Proteinmentioning
confidence: 99%
“…Recent work has demonstrated that U24-6A can be phosphorylated by MAPK, albeit less effectively than MBP13. It has also been shown that U24-6A can associate with Fyn SH3, but again does so more weakly than MBP ( K D  = 5 mM for U24-6A14 versus 4-8 μM for MBP15). These findings suggested that although U24-6A may mimic MBP, it most likely does not interfere directly with MBP function.…”
mentioning
confidence: 99%